Determinants of Dividend Policy of Real Estate, Property, and Building Construction Companies Listed in IDX with Unbalanced Panel Data Approach - Powell Gian Hartono; Anita Roosmalina Matusin (Universitas Airlangga, 2020)
This study involved companies engaging in real estate, property, and building construction companies listed in IDX for 2013 - 2019 period as the population. Unbalanced panel data regression was employed using the SPSS version 22 and E-Views version 10 to analyze the data and to test the hypotheses. The results showed that the previous year's dividend had a positive effect on dividend policy, while company size had a negative effect on dividend policy. This study proved that previous year's dividend and company size were key variables that determined companies’ dividend policy and they were major investment considerations for investors in order to obtain optimal returns.